Implementation and evaluation of a palliative care training unit for EMS providers - Hauch, Holger; El Mohaui, Naual; Sander, Michael; Rellensmann, Georg; Berthold, Daniel; Kriwy, Peter; Zernikow, Boris; Wager, Julia; Schneck, Emmanuel (Frontiers in Pediatrics, 2023)
Holger Hauch reviewed the literature, collected the data, performed the statistical analysis, contributed to ethics commission proposal and drafted the manuscript; Naual El Mohaui was responsible for data management and performed statistical analysis and drafted tables, Peter Kriwy, Daniel Berthold, Georg Rellensmann, Boris Zernikow, Julia Wager contributed to the statistical analysis, discussions, and reviewed the manuscript., Emmanuel Schneck reviewed the literature, discussed the data, and contributed to the drafting of the manuscript.